Biochemical Role of Homocysteine in Immune Modulation and Cytokine Dynamics in Acute Ischemic Stroke: Implications for Stroke-Associated Infections: Biochemical Analysis of Cytokine Dynamics in Acute Ischemic Stroke - Cai, Jiayi; Xu, Qiuxin; Shen, Haofeng (Journal of Medical Biochemistry, 2025)
Background: Ischemic stroke is a leading cause of morbidity and mortality, with immune dysregulation contributing to its progression. Elevated homocysteine (Hcy) levels are implicated in altering immune responses and increasing stroke severity. This study aimed to investigate the biochemical role of serum homocysteine in modulating immune responses, particularly cytokine profiles, and its association with post-stroke infections in patients with acute ischemic stroke.Methods: A cohort of 106 patients with acute ischemic stroke was divided into Low-, Medium-, and High-Hcy groups. Serum levels of cytokines (IL-6, IL-4, IFN-γ, IL-10) and immune modulation markers (e.g., IFN-γ/IL-4 ratio) were quantified. The presence of stroke-associated infections (SAI) was recorded, and its relationship with immune parameters was analyzed.Results: The High-Hcy group showed significantly higher serum levels of IL-6, IFN-γ, and IL-10 compared to the Low-Hcy group (P < 0.05), suggesting a pro-inflammatory bias. In patients with SAI, IL-4 levels were notably elevated, and the IFN-γ/IL-4 ratio indicated an immune suppressive trend. Although stroke severity was similar across groups, those with heightened immune dysregulation were more prone to infections.Conclusions: Elevated homocysteine levels induce a shift in immune responses by promoting pro-inflammatory cytokines while influencing anti-inflammatory pathways. This immune modulation is associated with an increased risk of post-stroke infections, emphasizing the dual role of cytokine dynamics in stroke pathophysiology. Targeting these biochemical pathways may present novel therapeutic strategies to mitigate stroke complications.
Keywords: Ischemic Stroke; Homocysteine; Cytokine Dynamics; Immune Modulation; Stroke-Associated Infection; Inflammatory Pathways